The Semiotic Study : Decoding the Symbolic Meaning of the Nokeso Tradition in the Salena Environment - Suparni, Suparni; Saputra, Rian (Pulchra Lingua: A Journal of Language Study, Literature & Linguistics, 2023)
This qualitative research explores the nokeso tradition in the Salena environment of Central Sulawesi, Indonesia. It aims to uncover the significance of the symbols within this cultural practice. Conducted in Tipo Village, Ulujadi District, Palu City, the study employed observation, recording, and interviews to gather evidence-based data. Nokeso is an indigenous tradition upheld by the Salena community, originating from the Kaili tribe. While traditionally associated with children entering adolescence, the research revealed that in Salena, it also involves the readiness of vati (male parents) of girls based on their social status. The nokeso ritual includes the symbolic act of tooth brushing, performed by Salena's traditional leaders using a whetstone or guma (traditional machete). The research findings highlight that the 16 tools used in nokeso carry distinct meanings, symbolizing positive outcomes and the well-being of toniasa (daughters) in the collective consciousness of the Salena people.